2009
DOI: 10.1002/clc.20499
|View full text |Cite
|
Sign up to set email alerts
|

Valvular Perforation in Left‐sided Native Valve Infective Endocarditis

Abstract: Background: Left-sided native valve infective endocarditis (LNVIE) can result in mitral (MP) and aortic (AP) valve perforation, the prognostic significance of which remains poorly defined. Hypothesis: Valvular perforation is associated with worse outcomes. Methods: Retrospective review of patients with LNVIE during 1998-2005 was performed to examine characteristics and outcome predictors of LNVIE complicated by valve perforation. Patients were stratified as: group A: MP or AP detected by transesophageal echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Even when surgery was accounted for in our multivariable model, the presence of an abscess was associated with in-hospital death and both perforation and abscess were associated with 1-year mortality in S. aureus LNVIE and streptococcal LNVIE. The finding that perforation is an independent marker of mortality concurs with a study conducted by Bachour and colleagues who found that a valve perforation complicating LNVIE is associated with high mortality in a retrospective review of 123 LNVIE cases [11]. Abscess is a life-threatening complication that cannot be cured with antibiotic therapy alone.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Even when surgery was accounted for in our multivariable model, the presence of an abscess was associated with in-hospital death and both perforation and abscess were associated with 1-year mortality in S. aureus LNVIE and streptococcal LNVIE. The finding that perforation is an independent marker of mortality concurs with a study conducted by Bachour and colleagues who found that a valve perforation complicating LNVIE is associated with high mortality in a retrospective review of 123 LNVIE cases [11]. Abscess is a life-threatening complication that cannot be cured with antibiotic therapy alone.…”
Section: Discussionsupporting
confidence: 80%
“…However, data for left ventricular ejection fraction (LVEF) and LV dimensions were not captured, yet may add incremental prognostic value in IE. Finally, inconsistencies exist regarding the causative pathogen and risk of tissue destruction such as fistulas, perforation or abscess formation [10,11]. …”
mentioning
confidence: 99%
“…[1][2][3][4][5] This was the most common etiology in our population, seen in 60% of the patients (Figs. [1][2][3][4][5] This was the most common etiology in our population, seen in 60% of the patients (Figs.…”
Section: Etiology and Location Of Aortic Valve Perforationmentioning
confidence: 99%
“…1,[3][4][5][8][9][10][11][12][13][14][15][16] The major strength of the recently introduced RT3DTEE is its ability to provide precise spatial orientation of cardiac anatomy; it also shows the interstructural spatial relationships and displays the aortic and mitral valve anatomy from the surgeon's perspective. 1,[3][4][5][8][9][10][11][12][13][14][15][16] The major strength of the recently introduced RT3DTEE is its ability to provide precise spatial orientation of cardiac anatomy; it also shows the interstructural spatial relationships and displays the aortic and mitral valve anatomy from the surgeon's perspective.…”
Section: D and Real Time 3dtee In Diagnosing Av Perforationmentioning
confidence: 99%
See 1 more Smart Citation